Validation of Saiful Anwar Clinical Congestion Score in Comparison with NT-proBNP for Prediction of Short-term Outcome in Acute Heart Failure with Reduced Ejection Fraction - Liemena Harold Adrian; Mohammad Saifur Rohman; Muhammad Rizki Fadlan; Cholid Tri Tjahjono; Anna Fuji Rahimah; Novi Kurnianingsih (Heart Science Journal, 2020)
Background : Risk stratification of acute heart failure (AHF) patient during hospital admission utilizing clinical scores emerges as an alternative to standart natriuretic peptide measurement. Development of Saiful Anwar clinical congestion score (SACS) as multivariable predictive model for prediction of short-term outcome in AHF with reduced ejection fraction (AHF-rEF) requires validation in comparison to NT-proBNP.Objective : To validate prognostic value of SACS compare with NT-proBNP in AHF-rEFMethod : This single-center, prospective cohort study was held in dr. Saiful Anwar General Hospital during January 2019 to June 2020. From total 89 AHF-rEF patients who admitted to emergency department, were assigned to SACS prospective questionnaire fulfillment and NT-proBNP measurement during first 12-hours since admission. Patients were divided into two groups based on SACS score and NT-proBNP value during admission. 90-days follow up was performed after index hospitalization with outcome of interest i.e all-cause mortality (ACM) and HF-related rehospitalization (HFR).Results : ACM and HFR rate in this study were 16.8% and 22.5%, respectively. SACS ≥6 demonstrated higher ACM and HFR rate during 90-days follow-up compared to SACS <6 (p=0.000; p=0.000, respectively). Performance of SACS ≥6 on admission showed good discriminative power for predicting 90-days ACM and HFR (AUC 0.841, p=0.000; AUC 0.788, p=0.000, respectively) compared to NT-proBNP ≥5000pg/mL (AUC 0.812, p=0.000; AUC 0.819, p=0.000, respectively). Additive value of NT-proBNP ≥5000pg/mL on top of SACS ≥6 increases discriminative power for predicting 90-days ACM and HFR after index hospitalization (AUC 0.836, p=0.000; AUC 0.90, p=0.000, respectively).Comclusion : SACS has demonstrated prognostic value compared to NT-proBNP for prediction of 90-days ACM and HFR after index hospitalization in AHF-rEF patients.